Rural Women's Health Information Needs: Are Technology-Based Services the Answer? - Wathen, Nadine C; Harris, Roma (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Various models of community health information delivery exist in Canada. Spiraling health care costs have many governments seeking to promote more judicious (and presumably more cost-effective) use of health care by consumers. One such method is through centralized, government-run health information services that rely heavily on information and communication technologies.